An Analysis of Sumbawa Vocational High Schools English Foreign Language Teachers’ English Proficiency - Rahmatul Iman, Topan; Fatmawati, Fatmawati; Winata, Efan Yudha (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
The aim of the study is to analyze the English proficiency of VHSs EFL teachers in Sumbawa. In Indonesia, English is considered a foreign language and a mandatory subject that has to be taught at schools. Especially at Vocational High School (VHS), neither current nor official records of English as a Foreign Language (EFL) teachers’ proficiency levels exists in our national databases (Yusuf and Novita, 2020). It could be argued that many English teachers in Indonesian schools fall under the category of less-skilled professionals with the lack of adequate competences to teach the language (Renandya, Hamid, & Nurkanto, 2018). The participants of the study consisted of 30 VHSs EFL Teachers of Sumbawa. The data collected using TOEFL like test, and it was analyzed in thre steps; correcting the TOEFL score, converting it into CEFR level, and intepreting the data. The results of the study show that the English proficiency of the VHSs EFL teachers is range from A1 to B1 which the majority of the participating teachers’ language proficiency are still at the CEFR A2 level. Regarding the strong points, it shows that the participants perform better at listening comprehension compared to the other two sets of skills tested. Based on the analysis of their numbers of correct answers, SWE section seemed to be a weak point for nearly every participant.